Microstructure and mechanical behavior of nanotwinned AlTi alloys with 9R phase. (15th April 2018) - Zhang, Y.F.; Xue, S.; Li, Q.; Fan, C.; Su, R.; Ding, Jie; Wang, Han; Wang, H.; Zhang, X.
Abstract: Nanotwinned metals have shown high strength and ductility. However, metals with high stacking fault energy, such as Al, typically do not contain high-density growth twins or stacking faults. Here we show that by using a small amount of Ti solutes, 0.15–5.1 at.%, fine grains with a large population of extended incoherent twin boundaries bounding broad 9R phase form in sputtered AlTi films. These nanotwinned AlTi films have hardness as high as 2 GPa. This study provides an alternative approach to design high-strength Al alloys by grain refinement and introducing high-density twin boundaries and 9R phase. Graphical abstract: Unlabelled Image